UN arms embargoes under scrutiny: Obstacles and options for an effective contribution to conflict resolution - Judith Vorrath (Stiftung Wissenschaft und Politik (SWP), 2024)
There are still a number of UN arms embargoes in place to prevent the flow of arms and military material into conflict zones. Although the UN Security Council is not generally deadlocked on this issue, it has only taken relevant decisions to re-design the embargoes in a few cases over the last ten years. Recent amending decisions have essentially created or extended exceptions or exemptions for the security forces of the respective national government. This is intended to strengthen them against non-state armed groups. Accompanying control mechanisms are increasingly controversial - both with the countries concerned and among the members of the Security Council. At the same time, meaningful political guidance on the embargoes and their adaptation to the respective conflict situation have proven to be difficult. This study focuses primarily on the relatively active UN arms embargoes on Somalia, Libya, the Democratic Republic of the Congo and the Central African Republic. For those, it reveals overarching challenges in implementation and enforcement: a) smuggling and irregular supplies, which also reflect the increasing internationalization of conflicts, b) exceptions and exemptions for government forces where there is a high risk of weapons being diverted from official stocks, and c) increased use of technologies such as drones and improvised explosive devices, whose components would have to be controlled as dual use goods. This suggests a need for further reforms of arms embargoes. Above all, however, they need to be better linked to political processes, especially those in the affected region. Arms embargoes can also be useful to obtain access to more or better information or as a bargaining chip vis-à-vis the internationally recognized government.
Keywords: 320; UN arms embargoes; UN Security Council; Somalia; Libya; Democratic Republic of the Congo; Central African Republic; preventing the flow of arms and military material into conflict zones